INTERPRETASI HADIS: ANTARA HERMENEUTIKA DAN SYARH AL-HADITS (STUDI KOMPARATIF) (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
This article attempts to analyze the syarh al-hadith method of classical and contemporary scholars and the hermeneutic method of Islamic scholars in explaining (interpreting) the Prophet's hadith. Because most scholars who write about the interpretation of hadith with a hermeneutics approach, instead use references in classical hadith syarh. Therefore, the author wants to examine the relevance of hermeneutical methods or theories in the study of syarh al-hadith. Is hermeneutics appropriate to be applied as a single foundation in the interpretation of hadith or is it only a complement to the syarh al-hadith? This article concludes after trying to compare the interpretations of the hadith commanding to fight humans until they say there is no god but Allah using the two approaches or methods above, and it turns out that both can go hand in hand and complement each other. Moreover, the hermeneutics approach is more about the meaning of the context of the hadith at the beginning of its emergence to the present, which requires an understanding of the meaning of the hadith according to its originator at the time of the background of the hadith (asbab wurud) and the history of this can be known through the syarah hadith method, especially, syarah hadith with other narrations or through the words of friends who lived contemporaries with the Prophet (originator). Besides that, the study of the original language of the text is also used as a reference in this case, which is part of the syarah of hadith as well. Artikel ini mencoba menganalisis metode syarah hadis ulama klasik dan kontemporer dan metode hermeneutika cendekiawan Islam dalam menjelaskan (menginterpretasi) hadis Nabi. Karena, kebanyakan cendekiawan yang menulis mengenai interpretasi hadis dengan pendekatan hermeneutika, justru menggunakan rujukan dalam syarah hadis klasik. Oleh karena itu, penulis ingin meneliti relevansi metode atau teori hermeneutika dalam kajian syarh al-hadits. Apakah hermeneutika layak diterapkan sebagai pondasi tunggal dalam interpretasi hadis ataukah hanya menjadi pelengkap syarh al-hadits? Artikel ini mengambil kesimpulan setelah mencoba membandingkan penafsiran terhadap hadis perintah memerangi manusia sampai mereka mengucapkan tiada Tuhan selain Allah dengan menggunakan dua pendekatan atau metode di atas.  Ternyata keduanya bisa berjalan beriringan dan saling melengkapi. Terlebih pendekatan hermeneutika lebih kepada pemaknaan konteks hadis di awal munculnya ke masa kini, yang mana hal itu memerlukan pemahaman akan makna hadis menurut pencetusnya di masa lahirnya hadis (asbab wurud) tersebut dan histori mengenai hal ini dapat diketahui melalui metode syarah hadis. Terutama syarah hadis dengan riwayat lainnya atau melalui perkataan Sahabat yang hidup sezaman dengan Nabi (pencetus). Di samping itu kajian bahasa asli teks juga dijadikan rujukan dalam hal ini, yang merupakan bagian dari syarah hadis juga.